2015
DOI: 10.1016/j.ijheatfluidflow.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and computational study of tip clearance effects on a transonic turbine stage

Abstract: This paper describes an experimental and computational investigation into the influence of tip clearance on the blade tip heat load of a high-pressure (HP) turbine stage. Experiments were performed in the Oxford Rotor facility which is a 1 1 2 stage, shroudless, transonic, high pressure turbine. The experiments were conducted at an engine representative Mach number and Reynolds number. Rotating frame instrumentation was used to capture both aerodynamic and heat flux data within the rotor blade row. Two rotor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The solid boundary on the 'casing' was treated as a slip wall since simulation of the boundarylayer on the casing was not part of this investigation; the influence of the casing with relative motion between blade tip and casing wall is a subject for future investigation. The effect of casing shear on the tip flow was the subject of a recent experimental investigation in a rotating transonic high-pressure turbine by Jackson et al (2015). In the study of Jackson et al (2015), experimental results were compared with computational simulations where a no-slip wall and a slip-wall were imposed on the casing.…”
Section: Numerical Set-up Of An Engine Scale Tip Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid boundary on the 'casing' was treated as a slip wall since simulation of the boundarylayer on the casing was not part of this investigation; the influence of the casing with relative motion between blade tip and casing wall is a subject for future investigation. The effect of casing shear on the tip flow was the subject of a recent experimental investigation in a rotating transonic high-pressure turbine by Jackson et al (2015). In the study of Jackson et al (2015), experimental results were compared with computational simulations where a no-slip wall and a slip-wall were imposed on the casing.…”
Section: Numerical Set-up Of An Engine Scale Tip Flowmentioning
confidence: 99%
“…The effect of casing shear on the tip flow was the subject of a recent experimental investigation in a rotating transonic high-pressure turbine by Jackson et al (2015). In the study of Jackson et al (2015), experimental results were compared with computational simulations where a no-slip wall and a slip-wall were imposed on the casing. The effect of casing shear was to change the tip-surface adiabatic wall temperature due to the effect of casing shear on the relative total temperature in the tip gap.…”
Section: Numerical Set-up Of An Engine Scale Tip Flowmentioning
confidence: 99%
“…In incompressible flow, the loss associated with the tip-leakage flow typically accounts for one third of the overall loss of a turbine stage [2]. Additionally, tip-leakage flows can lead to enhanced heat transfer in the tip-clearance, reducing the turbine blade life in high-temperature gas turbines [3][4][5]. Consequently, a comprehensive body of literature exists on low speed tip-leakage flows.…”
Section: Introductionmentioning
confidence: 99%
“…As for the transonic tip, Gao et al (2016) numerically studied the effect of tip clearance variation on transonic tip aerothermal characteristics. Zhang et al (2011) and Jackson et al (2015) performed closely combined experimental and numerical studies on transonic blade tips independently, and both concluded that changes in tip clearance have different influences on the aerothermal performance of the tip frontal region and the trailing edge due to different flow structures. Maesschalck et al (2014) also numerically investigated the aerothermal characteristics Aerothermal performance under tight tip clearances less than 0.5 per cent of the blade span, and the results showed that the aerothermal performance of the overtip region has a novel change, which provides new physical insights.…”
Section: Introductionmentioning
confidence: 99%